2010
DOI: 10.1016/s0924-9338(10)70864-6
|View full text |Cite
|
Sign up to set email alerts
|

P03-14 - A Quasi-Experimental Controlled Intervention to Reduce Violence on an Acute Psychiatric Ward

Abstract: Introduction: Violence and aggression are a major concern in acute inpatient psychiatric wards. Hard outcome data on the impact of service change are scarce. This poster presents the outcomes of service changes designed to improve the acute ward environment and patient experience. Aims and objectives: To implement changes to the delivery of acute inpatient psychiatric services and to measure the outcome of these changes in objective verifiable form. Method: Significant changes were introduced to an acute psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The literature shows that the specialisation of care approach (SC) is expected to simplify the practical organization of services, support quick clinical decision-making, enable clinical teams and clinicians to focus on only one setting, and foster an expertise in setting specific aspects of treatment [2,4,10]. On the one hand, proponents of this approach claim that the increasing specialisation of psychiatric services represents a progress in our understanding of mental health problems [9].…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that the specialisation of care approach (SC) is expected to simplify the practical organization of services, support quick clinical decision-making, enable clinical teams and clinicians to focus on only one setting, and foster an expertise in setting specific aspects of treatment [2,4,10]. On the one hand, proponents of this approach claim that the increasing specialisation of psychiatric services represents a progress in our understanding of mental health problems [9].…”
Section: Introductionmentioning
confidence: 99%
“…This care approach is expected to simplify the practical organisation of services; support quick clinical decision-making; enable clinical teams and clinicians to have a full focus on only one setting; and foster an expertise in setting specific aspects of treatment. 1 6 …”
Section: Introductionmentioning
confidence: 99%
“…No randomized controlled trials were identified. There were 13 nonrandomized comparative studies which compared outcomes of continuity and specialisation systems [2,1,14,16,[19][20][21][22]26,27,30,29,31,[36][37][38]40], three survey studies which investigated patient and staff views towards continuity and specialisation systems [3,15,35], and one qualitative semi-structured interview study on staff views towards the two systems [17]. NRT: non-randomized controlled trials; CBA: controlled before and after studies; C: continuity system; S: specialisation system.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…This ranged from comparing systems in which all staff members either worked across inpatient and outpatient settings or within one particular setting; to consultant-based systems (mainly in the UK) which focused only on continuity versus specialisation of consultant psychiatrists. The majority of studies collected data on psychiatric patients [2,1,14,16,19,20,22,26,27,30,29,31,[36][37][38]40,3], although three focused on staff [21,15,17], and one study included both patients and staff [35].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation